The Deliveries Chain and Value Added in Context of Coopetition Between the Service and Industrial Companies in Poland and UE (European Journal of Marketing and Economics, 2023)
In an activity of companies in Poland there is a problem in expansion of the small and medium- sized enterprises which can face difficulties with their development on both the domestic and international scene in relation to big economic entities. With reference to the above, as far as a financial situation of the researched companies or more precisely their expansion is concerned we should exert every effort to make connections between small and medium- sized enterprises of service character and big economic entities which produce material products. The aim of the article is to do the analysis in relation to selected enterprises from the SME’s sector which have their registered addresses in Poland and which cooperate with big companies and with the economic entities from other countries of the European Union in order to prove that the main principle is to increase expansion of the researched economic entities and that the cooperation between small and medium- sized firms and big holdings or concerns should be intensified especially when they refer to Poland and other countries of the European Union. Coopetition between the researched companies in that case should contribute to improvement in functioning of the deliveries chain and to increase in the Market Value Added (MVA) which is working out by both the small and medium- sized service enterprises and big industrial companies.
Keywords: deliveries chain, value added, company, enterprise coopetition